An alternative ethics for research: Levinas and the unheard voices and unseen faces. Issue 5 (3rd September 2017) - Vermeylen, Saskia; Clark, Gordon
Abstract: Some social scientists have criticised the workings of research-ethics committees on the grounds that their biomedical model is ill-suited to some social-science research in both practical and philosophical terms. In this paper we review these criticisms and propose an alternative approach to pre-research ethical review that is based on the philosophy of Emmanuel Levinas.